Influence of Wi-Fi service quality towards tourists' satisfaction anddissemination of tourism experience / Noorhaiza Masri, Faiz Izwan Anuar and Astri Yulia - Masri, Noorhaiza; Anuar, Faiz Izwan; Yulia, Astri (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Despite the heavy reliance on Wireless Fidelity (Wi-Fi) among tourists', and the increase number of hotspots available at tourist attractions, limited research is available that investigates the service quality of Wi-Fi. This study investigated the dimension of service quality (SERVQUAL), Technology Acceptance Model (TAM) perceived ease of use and perceived usefulness, and their relationships with tourists' satisfaction and tourism experience with Wi-Fi technology at tourists' attractions. The results indicated that perceived ease of use, perceived usefulness, and service quality significantly linked with tourists' satisfaction. We also found a significant effect of service quality on tourist experience. Implications of these results suggest that the key attributes need to be investigated to better understand the tourist satisfaction on the service quality assessments. Hence, the destination managers should consider upgrading Wi-Fi services as well as maintaining quality WI-FI services to enhance tourists' experience at tourist attractions.